Caracterização e aplicação da casca residual do processamento da Jabuticaba - Moura, Cláudia de Andrade (2016)
Jabuticaba tree (Plinia sp.) is a native species that has been widely distributed in almost all regions of Brazil. Recently, different native fruits, including jabuticaba, have been a research aim in order to investigate the best benefit of its nutritional properties. In order to arouse new alternatives for better utilization of agro-industrial by-products with nutritional and functional properties, researchers are seeking to develop innovative and functional bioactive products. By this angle, this study aimed at evaluating whether different jabuticaba juice extraction processes applied to obtain peels interfered on its nutritional properties as well as on the subsequent dehydration in order to turn a nutrient-rich residue, agro-industrial benefitted, in a food product that can be attractive to the consumer, as well as easy to be handled, stored and transported. Thus, this study was divided into three phases: the first one was divided according to the acquisition of jabuticaba fruits, from two identified genotypes as: one genotype as acquired in Clevelândia farm (25°07'20" S and 52°19'15" W) and the other genotype from Verê farm (25°53'1'' S: 52° 55' 11'' W). The fruits underwent through extraction process by crushing and forced steam to obtain peels. Subsequently, peels were submitted to dehydration process in an oven with forced air circulation at 70 °C. Then, after being dehydrated, they were ground and sieved to an 80-mesh size to obtain powder. Analyses were carried out to evaluate the influence of these processes in bioactive compounds and their variations based on samples of fresh jabuticaba peels from each genotype, since they underwent through the extraction process and then dehydration. This research was based on physicochemical analyses of hydroalcoholic extracts of samples. Centesimal composition parameters were evaluated: total soluble solids (TSS), titratable acidity, pH, ash, fiber, protein and moisture content, bioactive compounds (phenols, flavonoids and anthocyanins) and antioxidant activity (DPPH, ABTS and FRAP). The way jabuticaba peel was extracted (fresh or dried - powder) did not influence the obtained physicochemical results, or antioxidant activities measured by ABTS and FRAP. Jabuticaba peels of both studied genotypes, extracted by crushing, showed the best contents concerning flavonoids, phenolic compounds and antioxidant activity by DPPH method. Jabuticaba peels of Clevelândia genotype showed the highest antioxidant content, flavonoids, phenolic, ABTS and FRAP. In the second moment of this trial, there was some effect of storage in anthocyanin content, antioxidant activity according to three different methods (DPPH, FRAP and ABTS), flavonoids, phenolic and physicochemical characteristics (moisture content, total acidity, pH, ashes, protein and fiber) of such waste powder (to obtain jabuticaba peel powder from both genotypes, extracted by steam and crushing). They also were vacuum packed and stored for 135 days. It was observed that the extraction by crushing showed the best results for DPPH activity according to the storage time and jabuticaba peel from Clevelândia genotype showed the highest antioxidant activity when compared to Verê genotype at the start time and over 135 storage days. Likewise this time has not changed, parameters as acidity and total protein content were obtained in both genotypes and their different extraction processes of jabuticaba powder peel. For the third phase, two evaluated waste samples were selected in phases I and II, which powder peel of Clevelândia genotype was extracted by forced-steam process (GCLV) while powder peel of Verê genotype was extracted by crushing (GVRE). Then, microbiological analyses were carried out (coliforms at 45 °C g-1, Salmonella spp. 25g-1 and yeasts and molds) with natural yogurt and selected powder peels of jabuticaba. Subsequently, four formulations were prepared and two of them were for each genotype: 3.6% GCLV and 1.8% GCLV while two ratios were for (3.6% / 1.8%) GVRE samples. The formulations were submitted to sensorial analyses of acceptability, purchase intent, frequency and reason for the evaluated product consumption, with 100 untrained consumers. The quality of jabuticaba peel color (Verê/Clevelândia genotypes) in powder was also evaluated after extraction xi (steam/crushing), and a*, b*, L*, C*, H* and Δab* color coordinates were analyzed. The dehydrated product and yogurt showed a low counting for filamentous fungi, yeasts, thermotolerant coliforms and absence of Salmonella spp., which indicates some good processing conditions. The addition of jabuticaba peel powder in yogurt resulted in good acceptance for samples such as 1.8g GCLV; 3.6g GCLV and 1.8g GVRE, whose answers varied from: I liked moderately and I liked very much . These samples received results of good intention to buy samples such as 1.8g GCLV, 3.6g GCLV and 1.8g GVRE. Concerning color, there was no effect on the quality of jabuticaba peel powder up to 135 storage days. Generally, the obtained peels by crushing showed the highest contents of flavonoids, phenolic compounds and antioxidant activity by DPPH method. Therefore, antioxidants of this product in yogurt is a promising alternative, since the results showed good rates for both genotypes and extraction treatments (steam/crushing). Wherefore, this process not only provides some proper disposal for waste but also uses important nutrients and natural dyes to add value to several kinds of foodstuff.